Failure of epoprostenol (prostacyclin, PGI2) to inhibit platelet aggregation and to prevent restenosis after coronary angioplasty: results of a randomised placebo controlled trial. Issue 1 (January 1994) - Gershlick, A. H.; Spriggins, D.; Davies, S. W.; Syndercombe Court, Y. D.; Timmins, J.; Timmis, A. D.; Rothman, M. T.; Layton, C.; Balcon, R.
Abstract : OBJECTIVE–To study the effect of epoprostenol (prostacyclin, PGI2) given before, during, and for 36 h after coronary angioplasty on restenosis at six months and to evaluate the transcardiac gradient of platelet aggregation before and after percutaneous transluminal coronary angioplasty (PTCA) in treated and placebo groups. DESIGN–Double blind placebo controlled randomised study. PATIENTS–135 patients with successful coronary angioplasty. METHODS–Intravenous infusion of PGI2 (4 ng/kg/ml) or buffer was started before balloon angioplasty and continued for 36 hours. Platelet aggregation was measured in blood from the aorta and coronary sinus before and after PTCA in each group. Routine follow up was at six months with repeat angiography and there was quantitative assessment of all angiograms (those undertaken within the follow up period and at routine follow up). PRESENTATION OF RESULTS–Restenosis rates in treated and placebo groups determined according to the National Heart, Lung and Blood Institute definition IV. Comparison at follow up between the effect of treatment on mean absolute luminal diameter and mean absolute follow up diameter in the placebo group. Comparison of acute gain and late loss between groups. RESULTS–Of 125 patients available for assessment 23 were re-admitted because of angina within the follow up period. Quantitative angiography showed restenosis in 15 (10 in the PGI2 group and five in the placebo group). Of 105 patients evaluated at six month angiography there was restenosis in nine more in the PGI2 group and 18 more in the placebo group. Total restenosis rates (for patients) were 29.2% for PGI2 and 38.3% for placebo (NS). The mean absolute gain in luminal diameter was 1.84 (0.76) mm in the PGI2 group and 1.58 (0.56) mm in the placebo group (p = 0.04); the late loss in the PGI2 group was also greater (0.65 (0.94) mm vs 0.62 (0.89) mm (NS) and there was no significant difference in final luminal diameter at follow up between the two groups (1.83 (0.88) mm v 1.59 (0.60) mm). The transcardiac gradient of quantitative platelet aggregation increased after PTCA in both groups, indicating that PGI2 in this dose did not affect angioplasty-induced platelet activation. Mean (SD) platelet activation indices in the PGI2 group were pre PTCA aorta 8.4 (4.1) v coronary sinus 8.8 (4.0) (p = 0.001) and post PTCA aorta 8.9(3.0) v coronary sinus 12.9 (5.7) (p = 0.001). In the placebo group the values were pre PTCA aorta 7.6 (3.3) v coronary sinus 7.4 (3.6) (p = 0.001) and post PTCA aorta 7.6(2.8) v coronary sinus 11.2(4.3) (p = 0.001). CONCLUSION–The dose of PGI2 given was designed to limit side effects and as a short-term infusion did not significantly decrease the six month restenosis rate after PTCA. The sample size, which was determined by the original protocol and chosen because of the potency of the agent being tested, would have detected only a 50% reduction in restenosis rate. There was, however, no effect in the treated patients on the increased platelet aggregation seen in placebo group as a result of angioplasty. Angioplasty is a powerful stimulus to blood factor activation. Powerful agents that prevent local platelet adhesion and aggregation are likely to be required to reduce restenosis.